INTERPERSONAL COMMUNICATION IN OVERCOMING THE PHUBBING BEHAVIOR PHENOMENON IN STUDENTS IN LHOKSEUMAWE CITY - Restiviani, Yuliana; Kholil, Syukur; Abdurrahman; Rahmad Alimin Lauli (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2023)
The effectiveness of communication has strong indications that it can overcome phubbing behavior. However, which factors are the most dominant in communication effectiveness is not yet known with certainty. This research aims to determine the effectiveness of communication factors that can overcome phubbing behavior among students in Lhokseumawe City, Aceh, Indonesia. The study’s population consisted of all teenagers in Lhokseumawe City actively studying at state universities in 2022, totaling 8,467 people. The sample included 382 students who met the inclusion criteria set by the researchers and according to a specific formula. This research employed quantitative methods with statistical tests involving Pearson correlation and multiple regression. The results revealed that Positiveness (X4) is the dominant factor significantly influencing the overcoming of phubbing behavior at Lhokseumawe City State University, as evidenced by a partial determination coefficient test value of 0.569 and a relative contribution value of 71.88%. This research contributes to contemporary communication studies and social pathology literature concerning phubbing behavior. It aids in developing communication theories, especially those related to communication psychology and effectiveness.